1999
DOI: 10.1007/s003740050506
|View full text |Cite
|
Sign up to set email alerts
|

Influence of inorganic and organic fertilization on soil microbial biomass, metabolic quotient and heavy metal bioavailability

Abstract: We studied the long-term effects (12 years) of municipal refuse compost addition on the total organic carbon (TOC), the amount and activity of the microbial biomass (soil microbial biomass C, B(C) and metabolic quotient qCO2) and heavy metal bioavaiability in soils as compared to manuring with mineral fertilizers (NPK) and farmyard manure (FYM). In addition, we studied the relationships between among the available fraction [Diethylenetriaminopentacetic acid (DTPA) extractable] of heavy metals and their total c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
72
0
11

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(93 citation statements)
references
References 28 publications
10
72
0
11
Order By: Relevance
“…No correlation between organic carbon and heavy metal content was confirmed. Consistent with our results, Leita et al (1999) reported that organic carbon probably does not reflect the heavy metal soil contamination. Wang et al (2007) found nonsignificant correlation between organic carbon and soil enzymes, which was probably due to the quality of the organic inputs into the soil.…”
Section: Index Of Geoaccumulation In Soilssupporting
confidence: 92%
“…No correlation between organic carbon and heavy metal content was confirmed. Consistent with our results, Leita et al (1999) reported that organic carbon probably does not reflect the heavy metal soil contamination. Wang et al (2007) found nonsignificant correlation between organic carbon and soil enzymes, which was probably due to the quality of the organic inputs into the soil.…”
Section: Index Of Geoaccumulation In Soilssupporting
confidence: 92%
“…Confirming the results of Kowalczyk and Schröder (1988) we found a positive correlation (r = 0.73) between dehydrogenase activity and microbial biomass. However, we cannot confirm that heavy metals, which are the most important inorganic pollutants added to soils with sewage and compost (Leita et al 1999), decrease the turnover rate of organic matter, presumably because of the inhibitory effects on microbial biomass and enzyme activity (Chandler et al 1995). …”
Section: Resultsmentioning
confidence: 87%
“…Influence of long-term application of organic wastes and mineral N fertilizer on soil pH, total N, C org , C mic and C mic /C org (soil samples were taken from the soil layer from 0-30 cm in spring 2006) clearly demonstrate that there were positive effects of organic amendments on microbiological soil parameters, it may be concluded that plant growth in our experiment was inhibited by the increased heavy metal content (Werner et al 1987). For this reason organic amendments must be viewed cautiously because of the increase of the soil content of toxic metals (Leita et al 1999). …”
Section: Resultsmentioning
confidence: 99%
“…One of the most common applied is rice straw (RS) compost. Although the importance of compost application for sustainable agriculture has been well documented by longterm fertilizer trials (Inoko 1984;Leita et aL 1999), little attention had been paid to the composting process from the viewpoint of soil microbiology.…”
mentioning
confidence: 99%